BUILDING SUSTAINABILITY INTO AGRICULTURAL SUPPLY CHAINS: WHAT ROLE FOR PRIVATE INTERNATIONAL LAW? - M.E. Tramhel , Jeanette (Direito.UnB - Revista de Direito da Universidade de Brasília, 2023)
This article considers certain private international law (PIL) instruments and how these might be used effectively to achieve greater sustainability in agricultural supply chains. After an overview of key concepts in sustainability, supply chains and the broader interpretation of PIL, investigation is made into the use of PIL as an immediate measure to keep supply chains open during crises such as pandemic or war. Taking the longer view, PIL instruments are considered for use to develop supply chains that are: 1) economically sustainable through improved access to credit; 2) environmentally sustainable through improved contract farming, and; 3) socially sustainable through land investment contracts. In the face of a governance gap for global supply chains, industry-led efforts through corporate social responsibility (CSR) are explored to consider whether agribusinesses that can demonstrate compliance with sustainable development parameters also meet the requirements of environmental, social and governance (ESG) factors to attract green finance and satisfy the demands of conscientious consumers through the use of Private Voluntary Standards (PVS). The question for reflection is what role PIL might have in strengthening such governance through the incorporation of international standards into binding contractual relationships to thereby foster sustainable agriculture and global food security.